Outcome of hepatitis B and C virus‐associated hepatocellular carcinoma occurring after renal transplantation. Issue 5 (5th December 2016) - Kanaan, N.; Raggi, C.; Goffin, E.; De Meyer, M.; Mourad, M.; Jadoul, M.; Beguin, C.; Kabamba, B.; Borbath, I.; Pirson, Y.; Hassoun, Z.
Summary: Kidney transplant recipients (KTR) are subjected to immunosuppressive therapy that can enhance hepatitis B and C virus replication, leading to cirrhosis and hepatocellular carcinoma (HCC). The aim of this study was to assess the prevalence and outcome of HCC in KTR. Case‐control study. Patients with chronic HBV and/or HCV infection who underwent kidney transplantation between 1976 and 2011 and subsequently developed HCC were compared to a control group of patients with chronic HBV and/or HCV infection, matched for gender and age at HCC diagnosis, who did not receive kidney transplantation. Among 2944 KTR, 330 had hepatitis B and/or C. Fourteen developed HCC, a period prevalence of 4.2%. Age at HCC diagnosis was 52.6 ± 6.5 years (53.5 ± 5.7 in controls, P =.76). Time between transplantation and HCC diagnosis was 16.7 ± 2.7 years. Six HCCs were related to HBV, six to HCV and two to co‐infection with HBV and HCV. Immunosuppressive therapy was comparable in HBV, HCV and HBV+HCV patients. At diagnosis, 71% of patients met Milan criteria (65% in the control group, P =.4). Alpha‐fetoprotein levels, tumour characteristics and treatment modalities were comparable between both groups. Patient survival 2 years after HCC diagnosis was 28% in KTR, compared to 68% in controls ( P =.024). Survival after HCC diagnosis is significantly worse in KTR compared to nontransplanted patients with HBV and/or HCV. Prevention is crucial and should be based on viral eradication/suppression before or after transplantation.